Preparation method and application of black halogen-free and phosphorus-free highly flame-retardant polyolefin heat shrinkable material

By adding SEBS, molybdenum disulfide and iron tetraoxide to the halogen-free phosphorus-free heat-shrinkage tube formula, and using coated modified intercalation hydrotalcite technology, the flame retardant and mechanical properties of existing heat-shrinkage tubes are solved. The problem has achieved efficient flame retardant and mechanical performance improvement.

CN118725446BActive Publication Date: 2025-02-11DONGGUAN QUANTAI IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410948324.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-16
Publication Date
2025-02-11
Estimated Expiration
2044-07-16

AI Technical Summary

Technical Problem

The existing halogen-free phosphorus-free heat shrinking tubes have shortcomings in flame retardant performance and mechanical properties, and it is difficult for users in the market to distinguish the differences between dividend phosphorus and organic phosphorus, making it difficult for products to be promoted.

Method used

Innovative addition of hydrogenated styrene-butadiene block copolymer (SEBS), molybdenum disulfide and iron tetraoxide to conventional halogen-free and phosphorus-free flame retardant formulations, and improve the use of coated modified intercalation hydrotalcite Compatibility of inorganic flame retardants with polymer substrates.

Benefits of technology

It achieves excellent flame retardant performance and good mechanical properties of the heat shrink tube, meets the VW-1 vertical combustion requirements in the UL224 standard, and reduces the peak heat release rate, total heat release and total smoke release.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004946367460000071
    Figure BDA0004946367460000071
  • Figure BDA0004946367460000081
    Figure BDA0004946367460000081
  • Figure BDA0004946367460000091
    Figure BDA0004946367460000091
Patent Text Reader

Abstract

The present invention relates to the technical field of halogen-free flame-retardant polyolefin heat shrinkable materials, and discloses a preparation method and application of a black halogen-free and phosphorus-free highly flame-retardant polyolefin heat shrinkable material. The preparation method of the heat shrinkable material comprises the following steps: a polymer substrate, a hydrogenated styrene-butadiene block copolymer, an inorganic flame retardant, melamine cyanurate, antimony trioxide, molybdenum disulfide, ferroferric oxide, a composite antioxidant, a processing aid and an environmentally friendly black masterbatch are successively added to a blender according to the proportion of each component, and stirred for 3-5 minutes; the mixture in the blender is placed in a mixer, heated to 105-115°C for mixing, and heated to 130-140°C for further mixing; the mixture in the mixer is placed in an extruder, and in an environment of 130-150°C, cold air is used for extrusion granulation to obtain a heat shrinkable material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of halogen-free flame-retardant polyolefin heat shrinkable materials, in particular to a preparation method and application of a black halogen-free and phosphorus-free highly flame-retardant polyolefin heat shrinkable material. Background Art

[0002] In order to meet the RoHS directive, manufacturers widely use coated red phosphorus to replace polybrominated biphenyls (PBB) and polybrominated diphenyl ethers (PBDE) to produce flame-retardant heat shrink tubing. When red phosphorus burns, it releases toxic and irritating smoke, corrodes human skin and mucous membranes, and endangers human health. When it is connected between the positive and negative poles of the circuit board, it will also react electrochemically with the metal copper and silver on the circuit board, connecting the positive and negative poles of the circuit board and causing circuit board failure. In June 2007, Apple released the "Apple Halogen-Free Specifications" to restrict the use of red phosphorus. In order to replace red phosphorus, manufacturers use organic phosphorus flame retardants such as diethyl aluminum hypophosphite or piperazine pyrophosphate to replace red phosphorus and develop halogen-free and red phosphorus-free heat shrink tubing products. Although halogen-free and red phosphorus-free products meet the requirements of red phosphorus-free, in fact, it is difficult for most users in the market to distinguish the difference between red phosphorus and organic phosphorus, and there are still major concerns, which makes it difficult for halogen-free and red phosphorus-free products to open up the market. However, flame retardants that do not contain halogen or phosphorus elements have extremely poor flame retardant effects and require extremely large filling amounts. Therefore, due to the flame retardant itself, it is extremely difficult to develop highly flame-retardant halogen-free and phosphorus-free heat shrink tubing with excellent mechanical properties and flame retardant properties.

[0003] Therefore, it is extremely necessary for those skilled in the art to provide a heat shrinkable tube that is easy to process and produce and has low cost, has excellent flame retardant properties, does not contain halogen and phosphorus elements, and has good mechanical properties.

[0004] Conventional polymer substrates will have poor mechanical properties and flexibility after adding a large amount of inorganic flame retardants, and low efficiency in extrusion and expansion processes. Hydrogenated styrene-butadiene block copolymer (SEBS) is a high-performance elastomer with good flexibility, high strength and high filling capacity. By adding SEBS to the formula, the flexibility and mechanical properties of the material can be improved, and the quality and production efficiency of heat shrinkable materials and tubes can be improved.

[0005] Adding 1-3% molybdenum disulfide and 1-3% ferrosoferric oxide to materials such as EVA can play a good synergistic flame retardant role, so that the oxygen index and vertical combustion grade of EVA composite materials are increased from 18% to 22% compared with pure EVA, and the flame retardant performance is improved to V-2. At the same time, the peak heat release rate, total heat release and total smoke release of EVA composite materials are reduced by 20%, 23% and 48% respectively compared with pure EVA. In addition, the addition of 1-3% molybdenum disulfide and 1-3% ferrosoferric oxide can increase the content of residues produced by the combustion of EVA composite materials by more than 10% compared with pure EVA.

[0006] The present invention innovatively adds SEBS, molybdenum disulfide and ferrosoferric oxide to the conventional halogen-free and phosphorus-free flame retardant formula, and the flame retardant of the prepared heat shrinkable tube meets the VW-1 vertical combustion requirement of the UL224 standard. Summary of the invention

[0007] The object of the present invention is to provide a preparation method and application of a black halogen-free and phosphorus-free highly flame-retardant polyolefin heat shrinkable material to solve the problems raised in the above background technology.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0009] The preparation method of a black halogen-free and phosphorus-free highly flame-retardant polyolefin heat shrinkable material comprises the following steps: adding a polymer substrate, a hydrogenated styrene-butadiene block copolymer (SEBS), an inorganic flame retardant, melamine cyanurate (MCA), antimony trioxide, molybdenum disulfide, ferrosirac oxide, a composite antioxidant, a processing aid and an environmentally friendly black masterbatch into a mixer in turn according to the proportion of each component, and stirring for 3-5 minutes; placing the mixture in the mixer in an internal mixer, heating it to 105-115°C for internal mixing, and heating it to 130-140°C for further internal mixing; placing the mixture in the internal mixer in an extruder, and extruding and granulating it with cold air in an environment of 130-150°C to obtain a heat shrinkable material.

[0010] Furthermore, the components in the heat shrinkable material are calculated by weight and include 80-100 parts of a polymer matrix, 5-15 parts of a hydrogenated styrene-butadiene block copolymer, 90-120 parts of an inorganic flame retardant, 15-30 parts of melamine cyanurate, 5-15 parts of antimony trioxide, 1-3 parts of molybdenum disulfide, 1-3 parts of ferrosoferric oxide, 3-5 parts of a composite antioxidant, 5-8 parts of a processing aid, and 3-5 parts of an environmentally friendly black masterbatch.

[0011] Furthermore, the proportions of the components in the polymer matrix are calculated by weight, including 5-15 parts of a radiation grafted compatibilizer grafted with maleic anhydride, 30-40 parts of an ethylene-vinyl acetate copolymer (EVA-1) with a vinyl acetate content of 14-18wt%, 20-30 parts of an ethylene-vinyl acetate copolymer (EVA-2) with a vinyl acetate content of 28wt%, and 20-30 parts of an ethylene-octene block copolymer (OBC).

[0012] Furthermore, the melt index MI of the ethylene-vinyl acetate copolymer is 2-6.

[0013] Furthermore, the ethylene-octene block copolymer has a melt index MI≤1.

[0014] Furthermore, the proportions of the components in the grafted maleic anhydride radiation grafted compatibilizer are calculated by weight, including 3-12 parts of grafted maleic anhydride ethylene-vinyl acetate copolymer (EVA-g-MAH) and 2-5 parts of grafted maleic anhydride ethylene-octene block copolymer (OBC-g-MAH).

[0015] Furthermore, the components in the composite antioxidant are calculated by weight, including 1-2 parts of a main antioxidant and 2-4 parts of an auxiliary antioxidant; wherein the main antioxidant includes any one or more of antioxidant 1010, antioxidant 1076, and antioxidant 1024; and the auxiliary antioxidant is any one or two of didodecyl thiodipropionate (antioxidant DLTP) and distearyl thiodipropionate (antioxidant DSTP).

[0016] Furthermore, the proportions of the components in the processing aid, by weight, include 1-2 parts of a cross-linking sensitizer and 4-6 parts of a lubricant.

[0017] Furthermore, the proportions of the components in the inorganic flame retardant, by mass, include 40-60 parts of aluminum hydroxide, 40-60 parts of magnesium hydroxide, and 10-20 parts of zinc borate.

[0018] Furthermore, the inorganic flame retardant further comprises 20-30 parts of modified intercalated hydrotalcite in terms of the proportion of each component by mass; the preparation method of the coated modified intercalated hydrotalcite comprises the following steps:

[0019] S1: Add acetylferrocene to tetrahydrofuran, stir evenly, add lithium aluminum hydride, stir at room temperature for 3-4h, add deionized water, filter, rotary evaporate, and recrystallize from petroleum ether to obtain hydroxyferrocene; add hydroxyferrocene and alumina particles to a reaction container, stir evenly, heat to 150-155°C in a vacuum environment for reaction for 6-7h, cool to room temperature, and introduce nitrogen to obtain vinylferrocene; add vinylferrocene, ethylene monomer, vinyl acetate, and azobisisobutyronitrile to toluene, heat to 60-70°C for reaction for 6-7h, add deionized water, filter, wash, and vacuum dry to obtain a ferrocene copolymer;

[0020] S2: adding ferrocene copolymer to sulfobutyl-β-cyclodextrin aqueous solution, monitoring by ultraviolet, stirring until ferrocene copolymer is encapsulated by sulfobutyl-β-cyclodextrin, dialyzing, freeze-drying to obtain grafted modified β-cyclodextrin; adding grafted modified β-cyclodextrin to deionized water, stirring evenly, preheating to 50-55°C, adding metal salt solution, adding 1 mol / L sodium hydroxide to adjust the pH to 9.8-10.2, stirring for 30-45 min, heating to 60-65°C for aging for 24 h, filtering, washing, and drying to obtain intercalated hydrotalcite;

[0021] S3: Add KH560 to an ethanol solution for pre-hydrolysis, add the intercalated hydrotalcite, heat to 70-75°C for reaction for 3-3.5h, filter, wash, and dry to obtain a silane coupling agent modified intercalated hydrotalcite; add the silane coupling agent modified intercalated hydrotalcite to deionized water, stir evenly, add melamine, heat to 95-98°C for reaction for 30-45min, add cyanuric acid and keep warm for reaction for 4-4.5h, cool to room temperature, filter, wash, and dry to obtain a coated modified intercalated hydrotalcite.

[0022] Furthermore, in the hydroxyferrocene, the mass ratio of acetylferrocene: lithium aluminum hydride is (4-5):1; in the vinyl ferrocene, the mass ratio of hydroxyferrocene: alumina particles is 1:(4-5); in the ferrocene copolymer, the mass ratio of vinyl ferrocene, ethylene monomer, and vinyl acetate is (1-2):(2-3):(4-6).

[0023] Furthermore, in the grafted modified β-cyclodextrin, the molar ratio of ferrocene in the ferrocene copolymer: β-cyclodextrin in sulfobutyl-β-cyclodextrin is 1:1; and the metal salt solution is composed of magnesium nitrate hexahydrate and aluminum nitrate nonahydrate dissolved in deionized water in a molar ratio of 2:1.

[0024] Furthermore, in the silane coupling agent modified intercalated hydrotalcite, the mass ratio of KH560: intercalated hydrotalcite is (2-3):1; in the coated modified intercalated hydrotalcite, the mass ratio of silane coupling agent modified intercalated hydrotalcite: melamine: cyanuric acid is (1-3):2:4.

[0025] Furthermore, the application of the heat shrinkable material in the field of heat shrinkable tubes and the preparation method of the heat shrinkable tubes include the following steps:

[0026] The heat shrinkable material is added into a φ30-90 single screw extruder, heated to 120-150°C for melt extrusion, radiation cross-linked, and heated for expansion to obtain a heat shrinkable tube.

[0027] Furthermore, the radiation cross-linking radiation source is an electron beam, the electron beam energy is 1-5 MeV, and the radiation dose is 80-150 kGy.

[0028] Furthermore, the heat shrinkable material is used in the field of heat shrinkable tubes. The heat shrinkable tubes prepared from the heat shrinkable material have mechanical and aging properties that meet the 125°C temperature resistance requirement of the UL224 standard (158°C / 168h aging), and the flame retardant properties meet the UL224 (VW-1) vertical burning standard.

[0029] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0030] The present invention adds a hydrogenated styrene-butadiene block copolymer high-performance elastomer to improve the elasticity and mechanical properties of the heat shrinkable tube, and further adds molybdenum disulfide and ferrosirconium tetroxide to play a good synergistic flame retardant role, thereby improving the flame retardant performance, while reducing the peak value of the heat release rate, the total heat release and the total smoke release of the heat shrinkable material and the tube, thereby improving the environmental protection performance of the heat shrinkable tube.

[0031] The present invention is based on the previous method to further improve the compatibility between inorganic flame retardants and polymer substrates, so as to achieve the purpose of improving the mechanical properties and flame retardant properties of heat shrinkable materials. The present invention uses MgAl hydrotalcite as the base material, grafts modified β-cyclodextrin as the intercalation modifier to perform intercalation modification treatment on it, then uses a silane coupling agent to modify the surface of MgAl hydrotalcite, and finally coats melamine cyanurate on the surface of MgAl hydrotalcite to prepare a coated modified intercalation hydrotalcite. Adding it to the polymer substrate as an additional inorganic flame retardant can effectively improve the compatibility between the flame retardant component filler and the polymer substrate in the heat shrinkable material, and improve the mechanical properties and flame retardant properties of the heat shrinkable material. The present invention prepares vinyl ferrocene by acetyl ferrocene, and then uses vinyl ferrocene, ethylene monomer, and vinyl acetate as raw materials for free radical random copolymerization, and successfully prepares ethylene-vinyl acetate copolymer containing ferrocene structure, and it is included with sulfobutyl-β-cyclodextrin through self-assembly to prepare intercalation hydrotalcite. The present invention is different from the traditional method of first inserting sulfobutyl-β-cyclodextrin into hydrotalcite and then encapsulating it with ferrocene. The present invention assembles ethylene-vinyl acetate copolymer containing ferrocene structure and sulfobutyl-β-cyclodextrin before performing intercalation treatment, which can effectively avoid the limitation of the assembly and encapsulation effect between ethylene-vinyl acetate copolymer containing ferrocene structure and sulfobutyl-β-cyclodextrin, greatly improves the intercalation modification efficiency, and improves the compatibility and dispersibility of intercalated hydrotalcite in polymer matrix. The triple effects of combining the structure of hydrotalcite itself, the siloxane grafted melamine cyanurate coating modification treatment on the surface of hydrotalcite, and the intercalation modification of hydrotalcite can improve the dispersibility and compatibility of inorganic flame retardants aluminum hydroxide and magnesium hydroxide in the polymer matrix, and at the same time, the flame retardant component filler in the heat shrink material is coordinated to further improve the flame retardant property of the heat shrink material. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] In the following examples, sulfobutyl-β-cyclodextrin was purchased from Shanghai Yuanye Biotechnology Co., Ltd.; acetylferrocene was purchased from Hubei Hengjingrui Chemical Co., Ltd.; MgAl hydrotalcite was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; EVA-g-MAH, OBC-g-MAH, and radiation grafted compatibilizer grafted with maleic anhydride were purchased from the Shanghai Institute of Applied Physics, Chinese Academy of Sciences; EVA1 model: EVA4110J, VA=14, MI=2-3; EVA2 model: EVA6110M, VA=28, MI=6, purchased from Yangzi Petrochemical-BASF Co., Ltd.; OBC model: OBC NFUSE 9000, MI=0.5, purchased from Dow Chemical, USA; SEBS model: SEBS G1651, purchased from Kraton, USA; silicone masterbatch model: GT-300, purchased from Zhejiang Jiahua Fine Chemical Co., Ltd.; the remaining raw materials are all commercially available.

[0034] Each embodiment and comparative example prepared a heat shrinkable material according to the formula in Table 1 below;

[0035] Embodiment, comparative example Preparation process of heat shrinkable material: Add polymer substrate, hydrogenated styrene-butadiene block copolymer, inorganic flame retardant, melamine cyanurate, antimony trioxide, molybdenum disulfide, ferrosirac, composite antioxidant, processing aid and environmentally friendly black masterbatch into a mixer in turn according to the proportion of each component, and stir for 3 minutes; place the mixture in the mixer in an internal mixer, heat to 105°C for internal mixing, and continue to mix at 130°C; place the mixture in the internal mixer in an extruder, extrude and granulate with cold air in an environment of 130°C to obtain a heat shrinkable material.

[0036] Embodiment, comparative example The preparation process of the heat shrinkable tube is as follows: the heat shrinkable material is added into a φ30 single screw extruder, heated to 120° C. for melt extrusion, radiation cross-linked, and heated for expansion to obtain a heat shrinkable tube.

[0037] The radiation source for the radiation cross-linking is an electron beam, the electron beam energy is 1 MeV, and the radiation dose is 80 kGy.

[0038] Embodiment, comparative example A method for preparing a modified intercalated hydrotalcite coated in a heat shrinkable material comprises the following steps: S1: adding 5 g of acetylferrocene to tetrahydrofuran, stirring evenly, adding 1 g of lithium aluminum hydride, stirring at room temperature for 3 h, adding deionized water, filtering, rotary evaporation, and recrystallization from petroleum ether to obtain hydroxyferrocene; adding 1 g of hydroxyferrocene and 5 g of alumina particles to a reaction container, stirring evenly, heating to 150° C. under a vacuum environment for reaction for 6 h, cooling to room temperature, and introducing nitrogen to obtain vinylferrocene; adding 1 g of vinylferrocene, 2 g of ethylene monomer, 4 g of vinyl acetate, and 0.5 g of azobisisobutyronitrile to toluene, heating to 60° C. for reaction for 6 h, adding deionized water, filtering, washing, and vacuum drying to obtain a ferrocene copolymer;

[0039] S2: Add ferrocene copolymer to sulfobutyl-β-cyclodextrin aqueous solution, monitor under ultraviolet, stir until ferrocene copolymer is encapsulated by sulfobutyl-β-cyclodextrin, dialyze, freeze-dry, and obtain grafted modified β-cyclodextrin; add grafted modified β-cyclodextrin to deionized water, stir evenly, preheat to 50°C, add metal salt solution, add 1 mol / L sodium hydroxide to adjust pH to 10, stir for 30 min, heat to 60°C and age for 24 h, filter, wash, and dry to obtain intercalated hydrotalcite; wherein the metal salt solution is composed of 10 mmol magnesium nitrate hexahydrate and 5 mmol aluminum nitrate nonahydrate dissolved in deionized water;

[0040] S3: Add 3g KH560 to ethanol solution for pre-hydrolysis, add 1g intercalated hydrotalcite, heat to 70°C for reaction for 3h, filter, wash, and dry to obtain silane coupling agent modified intercalated hydrotalcite; add 2g silane coupling agent modified intercalated hydrotalcite to deionized water, stir evenly, add 2g melamine, heat to 95°C for reaction for 30min, add 4g cyanuric acid and keep warm for reaction for 4h, cool to room temperature, filter, wash, and dry to obtain coated modified intercalated hydrotalcite.

[0041] Comparative Example 5: Preparation method of coated modified intercalated hydrotalcite: S1: Add 5g of acetylferrocene to tetrahydrofuran, stir evenly, add 1g of lithium aluminum hydride, stir at room temperature for 3h, add deionized water, filter, rotary evaporate, and recrystallize from petroleum ether to obtain hydroxyferrocene; add 1g of hydroxyferrocene and 5g of alumina particles to a reaction container, stir evenly, heat to 150°C under vacuum environment for reaction for 6h, cool to room temperature, and introduce nitrogen to obtain vinylferrocene; add 1g of vinylferrocene, 2g of ethylene monomer, 4g of vinyl acetate, and 0.5g of azobisisobutyronitrile to toluene, heat to 60°C for reaction for 6h, add deionized water, filter, wash, and vacuum dry to obtain a ferrocene copolymer;

[0042] S2: Add sulfobutyl-β-cyclodextrin to deionized water, stir evenly, preheat to 50°C, add metal salt solution, add 1 mol / L sodium hydroxide to adjust the pH to 10, stir for 30 min, heat to 60°C and age for 24 h, filter, wash, and dry to obtain hydrotalcite; wherein the metal salt solution is composed of 10 mmol magnesium nitrate hexahydrate and 5 mmol aluminum nitrate nonahydrate dissolved in deionized water; add ferrocene copolymer to methanol aqueous solution and stir evenly, add hydrotalcite, ultrasonically disperse, adsorb for 24 h, filter, wash, and dry to obtain intercalated hydrotalcite;

[0043] S3: Add 3g KH560 to ethanol solution for pre-hydrolysis, add 1g intercalated hydrotalcite, heat to 70°C for reaction for 3h, filter, wash, and dry to obtain silane coupling agent modified intercalated hydrotalcite; add 2g silane coupling agent modified intercalated hydrotalcite to deionized water, stir evenly, add 2g melamine, heat to 95°C for reaction for 30min, add 4g cyanuric acid and keep warm for reaction for 4h, cool to room temperature, filter, wash, and dry to obtain coated modified intercalated hydrotalcite.

[0044] Comparative Example 6: Preparation method of coated modified intercalated hydrotalcite: S1: Add 5g of acetylferrocene to tetrahydrofuran, stir evenly, add 1g of lithium aluminum hydride, stir at room temperature for 3h, add deionized water, filter, rotary evaporate, and recrystallize from petroleum ether to obtain hydroxyferrocene; add 1g of hydroxyferrocene and 5g of alumina particles to a reaction container, stir evenly, heat to 150°C under vacuum environment for reaction for 6h, cool to room temperature, and introduce nitrogen to obtain vinylferrocene; add 1g of vinylferrocene, 2g of ethylene monomer, 4g of vinyl acetate, and 0.5g of azobisisobutyronitrile to toluene, heat to 60°C for reaction for 6h, add deionized water, filter, wash, and vacuum dry to obtain a ferrocene copolymer;

[0045] S2: Add ferrocene copolymer to sulfobutyl-β-cyclodextrin aqueous solution, monitor under ultraviolet, stir until the ferrocene copolymer is encapsulated by sulfobutyl-β-cyclodextrin, dialyze, freeze-dry, and obtain grafted modified β-cyclodextrin; add grafted modified β-cyclodextrin to deionized water, stir evenly, preheat to 50°C, add metal salt solution, add 1 mol / L sodium hydroxide to adjust the pH to 10, stir for 30 minutes, heat to 60°C and age for 24 hours, filter, wash, and dry to obtain coated modified intercalated hydrotalcite; wherein the metal salt solution is composed of 10 mmol magnesium nitrate hexahydrate and 5 mmol aluminum nitrate nonahydrate dissolved in deionized water.

[0046] Table 1 Composition of ingredients for examples and comparative examples

[0047]

[0048]

[0049] Experiment: The heat shrinkable materials prepared in the above embodiments and comparative examples were tested according to the cross-linked temperature-resistant 125°C model requirements in the GB / T32129-2015 standard. The experimental data are shown in Table 2 below;

[0050] The heat shrinkable tubes prepared in the above examples and comparative examples were tested according to the UL224-2006 standard. The experimental data are shown in Table 3 below.

[0051] Table 2 Experimental test data of heat shrinkage materials

[0052]

[0053] Table 3 Heat shrink tube experimental test data table

[0054]

[0055]

[0056] Conclusion: The heat shrinkable material prepared by the present invention and the heat shrinkable tube prepared using the heat shrinkable material as raw material have excellent mechanical properties and flame retardant properties. The additional addition of coated modified intercalated hydrotalcite can further improve the mechanical properties and flame retardant properties of the material.

[0057] Compared with Example 1, Comparative Example 1 lacks SEBS, resulting in reduced flame retardancy. Compared with Example 1, Comparative Examples 2 and 3 lack molybdenum disulfide and ferroferric oxide, resulting in reduced flame retardancy. Compared with Example 3, in the process of preparing the coated modified intercalated hydrotalcite, Comparative Example 4 adopts the method of first intercalating β-cyclodextrin and then encapsulating ferrocene polymer, resulting in reduced encapsulation efficiency, resulting in reduced mechanical properties and flame retardancy. Compared with Example 3, Comparative Example 5 lacks silane coupling agent modification and MCA coating treatment, resulting in reduced compatibility and dispersibility, and reduced mechanical properties and flame retardancy. Compared with Example 3, Comparative Example 6 uses unmodified hydrotalcite instead of coated modified intercalated hydrotalcite, resulting in reduced compatibility and dispersibility, and reduced mechanical properties and flame retardancy.

[0058] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a black halogen-free and phosphorus-free highly flame-retardant polyolefin heat shrinkable material, characterized in that: The method comprises the following steps: adding a polymer substrate, a hydrogenated styrene-butadiene block copolymer, an inorganic flame retardant, melamine cyanurate, antimony trioxide, molybdenum disulfide, ferrosoferric oxide, a composite antioxidant, a processing aid and an environmentally friendly black masterbatch into a mixer in turn according to the proportion of each component, and stirring for 3-5 minutes; placing the mixture in the mixer in an internal mixer, heating it to 105-115° C. for internal mixing, and heating it to 130-140° C. for further internal mixing; placing the mixture in the internal mixer in an extruder, extruding and granulating it with cold air in an environment of 130-150° C. to obtain a heat shrinkable material; The components of the heat shrinkable material are calculated by weight, including 80-100 parts of polymer matrix, 5-15 parts of hydrogenated styrene-butadiene block copolymer, 90-120 parts of inorganic flame retardant, 15-30 parts of melamine cyanurate, 5-15 parts of antimony trioxide, 1-3 parts of molybdenum disulfide, 1-3 parts of ferrosoferric oxide, 3-5 parts of composite antioxidant, 5-8 parts of processing aid, and 3-5 parts of environmentally friendly black masterbatch; The proportions of the components in the inorganic flame retardant are calculated by weight, including 40-60 parts of aluminum hydroxide, 40-60 parts of magnesium hydroxide, and 10-20 parts of zinc borate; The inorganic flame retardant comprises 20-30 parts of modified intercalated hydrotalcite in proportions by mass. The method for preparing the coated modified intercalated hydrotalcite comprises the following steps: S1: Add acetylferrocene to tetrahydrofuran, stir evenly, add lithium aluminum hydride, stir at room temperature for 3-4h, add deionized water, filter, rotary evaporate, and recrystallize from petroleum ether to obtain hydroxyferrocene; add hydroxyferrocene and alumina particles to a reaction container, stir evenly, heat to 150-155°C in a vacuum environment for reaction for 6-7h, cool to room temperature, and introduce nitrogen to obtain vinylferrocene; add vinylferrocene, ethylene monomer, vinyl acetate, and azobisisobutyronitrile to toluene, heat to 60-70°C for reaction for 6-7h, add deionized water, filter, wash, and vacuum dry to obtain a ferrocene copolymer; S2: adding ferrocene copolymer to sulfobutyl-β-cyclodextrin aqueous solution, monitoring by ultraviolet, stirring until ferrocene copolymer is encapsulated by sulfobutyl-β-cyclodextrin, dialyzing, freeze-drying to obtain grafted modified β-cyclodextrin; adding grafted modified β-cyclodextrin to deionized water, stirring evenly, preheating to 50-55°C, adding metal salt solution, adding 1 mol / L sodium hydroxide to adjust the pH to 9.8-10.2, stirring for 30-45 min, heating to 60-65°C for aging for 24 h, filtering, washing, and drying to obtain intercalated hydrotalcite; S3: adding KH560 to an ethanol solution for pre-hydrolysis, adding intercalated hydrotalcite, heating to 70-75°C for reaction for 3-3.5h, filtering, washing, and drying to obtain silane coupling agent modified intercalated hydrotalcite; adding silane coupling agent modified intercalated hydrotalcite to deionized water, stirring evenly, adding melamine, heating to 95-98°C for reaction for 30-45min, adding cyanuric acid and keeping warm for reaction for 4-4.5h, cooling to room temperature, filtering, washing, and drying to obtain coated modified intercalated hydrotalcite; The components in the polymer matrix are calculated by weight, including 5-15 parts of a radiation grafted compatibilizer grafted with maleic anhydride, 30-40 parts of an ethylene-vinyl acetate copolymer having a vinyl acetate content of 14-18 wt%, 20-30 parts of an ethylene-vinyl acetate copolymer having a vinyl acetate content of 28 wt%, and 20-30 parts of an ethylene-octene block copolymer; The proportion of each component in the radiation grafted compatibilizer grafted with maleic anhydride is calculated by weight, including 3-12 parts of grafted maleic anhydride ethylene-vinyl acetate copolymer and 2-5 parts of grafted maleic anhydride ethylene-octene block copolymer; In the preparation process of hydroxyferrocene, the mass ratio of acetylferrocene: lithium aluminum hydride is (4-5):1; in the preparation process of vinylferrocene, the mass ratio of hydroxyferrocene: alumina particles is 1:(4-5); in the preparation process of ferrocene copolymer, the mass ratio of vinylferrocene, ethylene monomer, and vinyl acetate is (1-2):(2-3):(4-6); In the preparation process of the grafted modified β-cyclodextrin, the molar ratio of ferrocene in the ferrocene copolymer to β-cyclodextrin in the sulfobutyl-β-cyclodextrin is 1:1; the metal salt solution is composed of magnesium nitrate hexahydrate and aluminum nitrate nonahydrate dissolved in deionized water in a molar ratio of 2:1; In the preparation process of silane coupling agent modified intercalated hydrotalcite, the mass ratio of KH560: intercalated hydrotalcite is (2-3):1; in the preparation process of coated modified intercalated hydrotalcite, the mass ratio of silane coupling agent modified intercalated hydrotalcite: melamine: cyanuric acid is (1-3):2:

4.

2. The method for preparing the black halogen-free and phosphorus-free highly flame-retardant polyolefin heat shrinkable material according to claim 1, characterized in that: The proportions of the components in the composite antioxidant, calculated by mass, include 1-2 parts of a main antioxidant and 2-4 parts of an auxiliary antioxidant; wherein the main antioxidant includes any one or more of antioxidant 1010, antioxidant 1076, and antioxidant 1024; the auxiliary antioxidant is any one or two of didodecyl thiodipropionate and distearyl thiodipropionate; the proportions of the components in the processing aid, calculated by mass, include 1-2 parts of a cross-linking sensitizer and 4-6 parts of a lubricant.

3. Application of the heat shrinkable material prepared by the method for preparing black halogen-free and phosphorus-free highly flame-retardant polyolefin heat shrinkable material according to any one of claims 1 to 2 in the field of heat shrinkable tubes.

Citation Information

Patent Citations

  • High flame-retardant and high heat-resisting halogen-free expansion type fire-resistant cable material and preparation method thereof

    CN101735546A

  • Elastomer toughened cross-linked HDPE halogen-free smoke-suppression flame-retardant cable material and preparation method thereof

    CN115926288A